The politics of the German company network - Martin Höpner; Lothar Krempel (Max Planck Institute for the Study of Societies, 2003)
For over 100 years, the German company network was a major feature of organized corporate governance in Germany. This paper uses network visualization techniques and qualitative-historical analysis to discuss the structure, origins and development of this network and to analyze the reasons for its recent erosion. Network visualization makes it possible to identify crucial entanglement patterns that can be traced back historically. In three phases of network formation - the 1880s, 1920s and the 1950s -, capital entanglement resulted from the interplay of company behavior and government policy. In its heyday, the company network was de facto encompassing and provided its core participants, especially the banks, with a national, macroeconomic perspective. In the 1970s, a process of increased competition among financial companies set in. In the 1980s and 1990s, declining returns from blockholding and increased opportunity costs made network dissolution a thinkable option for companies. Because of the strategic reorientation of the largest banks toward investment banking, ties between banks and industry underwent functional changes. Since the year 2000, the German government's tax policy has sped up network erosion. Vanishing capital ties imply a declining degree of strategic coordination among large German companies. – – Ausgehend von einer Kombination von Netzwerkvisualisierung und historischer Analyse werden in diesem Papier Struktur, Entstehung und Entwicklung des deutschen Unternehmensnetzwerks sowie die Gründe für seine Erosion diskutiert. Die Visualisierungstechnik ermöglicht die Identifikation auffälliger Merkmale des Netzwerks, die anschließend geschichtlich zurückverfolgt werden können. In den drei Phasen der Netzwerkentstehung - den 1880er, 1920er und 1950er Jahren - resultierten Unternehmensverflechtungen aus einem Zusammenspiel von strategischen Unternehmensentscheidungen und Unterstützung auf politischer Ebene. In seiner Blütezeit umfasste das Netzwerk die größten deutschen Unternehmen und führte dazu, dass die Banken im Verflechtungskern eine nationale, makroökonomische Orientierung entwickelten. In den siebziger Jahren setzte ein Prozess zunehmender Konkurrenz unter Finanzunternehmen ein. In den achtziger und neunziger Jahren machten sinkende Erträge aus dem Halten großer Aktienpakete und gestiegene Opportunitätskosten die Netzwerkauflösung zu einer strategischen Option. Wegen der Umorientierung der Großbanken zum Investmentbanking unterlagen Verbindungen zwischen Banken und Industrie einem funktionalen Wandel. Seit dem Jahr 2000 unterstützte die Bundesregierung die Netzwerkauflösung steuerpolitisch. Dieser Prozess resultiert in einer rückläufigen strategischen Koordinierung zwischen großen deutschen Unternehmen.
Keywords: 300